2018
DOI: 10.1016/s1470-2045(17)30694-0
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab plus carboplatin and paclitaxel with or without bevacizumab versus carboplatin and paclitaxel with or without bevacizumab in advanced NSCLC (SWOG S0819): a randomised, phase 3 study

Abstract: National Cancer Institute and Eli Lilly and Company.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 30 publications
(55 reference statements)
2
56
0
Order By: Relevance
“…1 Greater than 80% of all lung cancer cases are non-small cell lung cancer (NSCLC), and >70% of patients have metastatic disease at the time of diagnosis. 2,3 Outcomes for patients with metastatic NSCLC are poor, with only 4% of patients surviving 5 years after diagnosis. 4,5 Before the introduction of targeted therapies and immunotherapy, platinum-doublet chemotherapy with or without bevacizumab was the standard of care for previously untreated patients with metastatic, nonsquamous NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…1 Greater than 80% of all lung cancer cases are non-small cell lung cancer (NSCLC), and >70% of patients have metastatic disease at the time of diagnosis. 2,3 Outcomes for patients with metastatic NSCLC are poor, with only 4% of patients surviving 5 years after diagnosis. 4,5 Before the introduction of targeted therapies and immunotherapy, platinum-doublet chemotherapy with or without bevacizumab was the standard of care for previously untreated patients with metastatic, nonsquamous NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a genetic driver mutation or expression of PD-L1, NCCN recommends several chemotherapy options, including cisplatin plus carboplatin plus gemcitabine, or a taxane for first-line intervention [7]. SWOG S0819 reconfirmed that paclitaxel plus carboplatin remains a treatment option for unselected patients [74]. In this trial, which evaluated paclitaxel plus carboplatin with or without cetuximab, there was no benefit to the addition of cetuximab regardless of histology.…”
Section: Scc: First-line Chemotherapymentioning
confidence: 99%
“…Further screening titles and abstracts, Finally, only 14 papers (8 papers about Gefitinib plus chemotherapy and 6 papers about Cetuximab plus chemotherapy) were included with excluding no-related researches. [18][19][20][21][22][23][24][25][26][27][28][29][30][31]…”
Section: Trial Flow Characteristic and Quality Assessment Of Includimentioning
confidence: 99%
“…Cetuximab has better prospects for treating advanced NSCLC, which may benefit patients with overall survival and progression-free survival [10]. Recently, many studies have shown that Gefitinib plus chemotherapy or Cetuximab plus chemotherapy are both superior to chemotherapy alone for advanced NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%